KEPUASAN PASIEN TERHADAP PELAYANAN DI TEMPAT PENDAFTARAN RAWAT JALAN RUMAH SAKIT UNIVERSITAS SUMATERA UTARA - IRAWATI, LENNI (LP2MTBM MAKARIOZ, 2021)
Hospitals as a health service are expected to provide satisfaction for patients. A hospital is a health service institution that provides comprehensive individual health services that provide inpatient, outpatient and emergency services. The health services provided are comprehensive services at the level of perfection of health services in creating a sense of self-satisfaction in each patient. The service in generating satisfaction is seen using five dimensions of service quality, namely the tangible dimensions of confidence, reliability (trust), responsiveness (ability). , assurance (Certainty), and empathy (empathy). To identify patient satisfaction with services at the outpatient registration site at the North Sumatra University Hospital. The type of research used is descriptive research with a quantitative approach and uses a cross-sectional data design. The samples taken were 98 patients using random sampling techniques. The data collection technique uses a questionnaire. Data analysis techniques use univariate analysis. based on research conducted from 98 respondents, patient satisfaction results showed that 5.10% of respondents said they were very satisfied, 87.76% said they were satisfied, 7.14% said they were quite satisfied. No respondents stated that they were dissatisfied or very dissatisfied. The highest satisfaction is in the tangibles dimension (85.71%) and the lowest satisfaction is in the empathy dimension (71.43%). In general, patients who receive services at the Outpatient Registration Center at the University of North Sumatra Hospital are satisfied with the services provided by registration officers, as evidenced by the results of patient satisfaction in the tangibles dimension of 85.71%, the reliability dimension of 73.47%, the responsiveness dimension was 74.49%, the assurance dimension was 80.61%, and the empathy dimension was 71.43%.